2018
DOI: 10.1186/s12974-018-1188-3
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid-specific TAK1 deletion results in reduced brain monocyte infiltration and improved outcomes after stroke

Abstract: BackgroundActivation of transforming growth factor-β-activated kinase 1 (TAK1) occurs after stroke and leads to an exacerbation of brain injury. TAK1 is involved in innate and adaptive immune responses, but it has divergent inflammatory effects that are dependent on the cell type in which it is activated. There is a robust infiltration of myeloid cells after stroke; however, the contribution of myeloid TAK1 to cerebral ischemia is currently unknown. We hypothesized that myeloid-specific deletion of TAK1 would … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 57 publications
1
8
0
Order By: Relevance
“…This study is the first evidence that shows the importance of peripheral MCs and their role in stroke in aged animals. Our group has previously shown that stroke leads to increased neuroinflammation in aged animals [35,36,56]. We have also shown that the gut is "inflamed" after stroke [35].…”
Section: Discussionmentioning
confidence: 93%
“…This study is the first evidence that shows the importance of peripheral MCs and their role in stroke in aged animals. Our group has previously shown that stroke leads to increased neuroinflammation in aged animals [35,36,56]. We have also shown that the gut is "inflamed" after stroke [35].…”
Section: Discussionmentioning
confidence: 93%
“…The regulation of transforming growth factor βactivated kinase 1 (TAK1), which is involved in both innate and adaptive immune responses and has conflicting inflammatory effects depending on the cell type, plays a key role in monocyte infiltration into the injury site following ischemic stroke. TAK1 deletion leads to reduced monocyte infiltration, thereby improving outcomes after ischemic stroke (115). In addition, Werner et al demonstrated that CXC motif chemokine receptor 4 (CXCR4) deficiency diminishes monocyte infiltration and dampens the levels of pattern recognition and defense response gene expression in monocyte-derived macrophages at the ischemic injury site, resulting in deteriorated ischemic stroke outcomes.…”
Section: Monocyte-derived Macrophagesmentioning
confidence: 99%
“…S6). TR4 acts in immunity, myelination, oligodendrocyte differentiation, learning and behavior [Chauhan et al, 2018; Zhang et al, 2018]. Thus, we ventured that rs75547282 may contribute to the risk of ASD by regulating the binding of the TIGD5 promoter region to TR4.…”
Section: Discussionmentioning
confidence: 91%